Growth of Pituitary Macroadenomas Postpartial Resection: Implications for Adjuvant Radiotherapy - Panet-Raymond, Valerie; Sabit, Kushraw; Shenouda, George; Sirhan, Denis; Zeitouni, Anthony; Souhami, Luis (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective To determine the volumetric growth in macroadenomas (MAs) patients with residual postoperative disease and to identify subpopulations with rapid postoperative growth rate that may benefit from early salvage radiotherapy (RT).Methods Patients who had undergone a partial resection for MAs and did not receive immediate postoperative RT were eligible. Residual tissue was contoured on serial magnetic resonance imaging and planimetric and volumetric changes in size were measured. Growth rates were established by a single observer using serial volumetric measurements. Data were analyzed to find a relationship among growth rate, adjuvant treatment, and patient and tumor characteristics.Results Thirty-one patients met the eligibility criteria. Nine patients (29%) required adjuvant treatment because of tumor growth. Volumetric growth was identified 95% of the time compared with 64% planimetrically. Planimetric growth could not be established in 10% of patients showing volumetric changes. Median growth rate was 0.4464 mL/y. Growth rate positively correlated with size of residual postoperative volume (p < 0.001). Receiving salvage treatment positively correlated with growth rate (p = 0.001), particularly at a rate above 2.19 mL/y (p = 0.0064). Five patients (16%) had a growth rate above this level, all of which required salvage treatment. Patients with postoperative residual volume > 3.95 mL were most likely to experience rapid growth rate and require salvage treatment (p = 0.007).Conclusion Volumetric measurement was found to be superior to planimetric measurement in detecting changes in patients with residual tumors. Patients with postoperative residual volume > 3.95 mL should be considered for early treatment with RT.
Keywords: pituitary; macroadenoma; radiotherapy; surgery; volumetric growth